Referral Practices for Cognitive Behavioral Therapy for Insomnia: A Survey Study - Deirdre A. Conroy; Matthew R. Ebben (Behavioural Neurology)
This study examined referring practices for cognitive behavioral therapy for insomnia (CBTI) by physicians at University of Michigan Hospitals and Weill Cornell Medical College of Cornell University. A five-item questionnaire was sent via email that inquired about the physician’s patient load, number of patients complaining of insomnia, percent referred for CBTI, and impressions of what is the most effective method for improving sleep quality in their patients with insomnia. The questionnaire was completed by 239 physicians. More physicians believed a treatment other than CBTI and/or medication was most effective (N = 83). “Sleep hygiene” was recommended by a third of the sample. The smallest number of physicians felt that CBTI alone was the most effective treatment (N = 22). Additional physician education is needed.